Computed tomographic angular measurements using a bone-centered three-dimensional coordinate system are accurate in a femoral torsional deformity model and precise in clinical canine patients - Brühschwein, Andreas; Schmitz, Bronson; Zöllner, Martin; Reese, Sven; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2023)
In small animal orthopedics, angular measurements in the canine femur are often applied in clinical patients with bone deformities and especially in complex and severe cases. Computed tomography (CT) has been shown to be more precise and accurate than two-dimensional radiography and several methods are described. Measurement techniques evaluated in normal bones must prove accuracy in deformed bones in clinical settings. Goals of our study were to evaluate the accuracy of canine femoral torsion angle measurements in a femoral torsional deformity model, and to test repeatability and reproducibility of canine femoral neck inclination, torsion and varus angle measurements in CT datasets of dogs applying a CT based technique using a three-dimensional (3D) bone-centered coordinate system. A femoral torsional deformity model was preset from 0° to +/ 90° rotation using goniometer measurements, and in their CT scans the simulated degree of torsional deformity was measured and compared with the preset reference standard. In CT data of 68 hind limbs of 34 dogs scanned in a clinical setting, the femoral neck inclination, torsion and varus angles were measured by two operators and the results were compared. In the femoral torsion model, Bland-Altman-Plots demonstrated a mean difference of 2.11°, and Passing-Bablok analysis demonstrated correlation between goniometer and CT based measurements. In the clinical CT scans, intra- and interobserver agreement resulted in coefficients of variation for repeated measurements (%) between 0.59 and 4.47 for the femoral neck inclination angles, between 1.06 and 5.15 for the varus angles and between 1.99 and 8.26 for the torsion angles. In conclusion, demonstration of precision for inclination, torsion and varus angle measurements in CT data of clinical patients does not proof accuracy, and accuracy in a torsional deformity model does not proof accuracy in complex angular bone deformities.